Formation of Interstellar Complex Organic Molecules on Water-rich Ices Triggered by Atomic Carbon Freezing - Stefano Ferrero; Cecilia Ceccarelli; Piero Ugliengo; Mariona Sodupe; Albert Rimola (The Astrophysical Journal, 2023)
The reactivity of interstellar carbon atoms (C) on water-dominated ices is one of the possible ways to form interstellar complex organic molecules (iCOMs). In this work, we report a quantum chemical study of the coupling reaction of C ( ^3 P) with an icy water molecule, alongside possible subsequent reactions with the most abundant closed-shell frozen species (NH _3 , CO, CO _2 , and H _2 ), atoms (H, N, and O), and molecular radicals (OH, NH _2 , and CH _3 ). We found that C reacts spontaneously with the water molecule, resulting in the formation of ^3 C–OH _2 , a highly reactive species due to its triplet electronic state. While reactions with the closed-shell species do not show any reactivity, reactions with N and O form CN and CO, respectively, the latter ending up in methanol upon subsequent hydrogenation. The reactions with OH, CH _3 , and NH _2 form methanediol, ethanol, and methanimine, respectively, upon subsequent hydrogenation. We also propose an explanation for methane formation observed in experiments through additions of H to C in the presence of ices. The astrochemical implications of this work are: (i) atomic C on water ice is locked into ^3 C–OH _2 , making difficult the reactivity of bare C atoms on icy surfaces, contrary to what is assumed in current astrochemical models; and (ii) the extraordinary reactivity of ^3 C–OH _2 provides new routes toward the formation of iCOMs in a nonenergetic way, in particular ethanol, the mother of other iCOMs once it is in the gas phase.